Аналіз небезпеки апаратних закладних пристроїв - Гриньов, Р. С. (ХНУРЕ, 2019)
Attacks on organizations using hardware embedded devices are a serious threat. Especially in Ukraine, where such things are still not widespread and are not perceived as a serious danger.